Evaluation of the Surface Contamination by Cytotoxic Agents of a Chemotherapy Reconstitution Unit: From Analysing Work Practices to Preventive and Corrective Actions - Drapeau Florent; Rossard Caroline; Darricau Béatrice; Hoarau Gilles; Bouscaren Nicolas; Hoarau Luciano; Rosbicki Sabrina; Chan- (De Gruyter, 2016)
The staff handling the cytotoxics are exposed to contamination as an occupational hazard. The unit of the Centre Hospitalier Universitaire (C.H.U) of Saint Pierre is ISO9001 certified. In a constant effort to improve the quality of our work, samples of the work surface were collected and allowed us, in a first step, to evaluate the contamination in a CRU in Reunion Island. As a result, corrective and preventive actions were implemented in the work routines.